Analysis of Vocational Lecturer’s Pedagogical Competence Needs for TVET: A Case Study on Vocational Lecturers in West Java, Indonesia - Komaro, Mumu; Maknun, Johar; ., Saripudin; Haritman, Erik; Suryana, Asep; Rokhim, Ismail; Heryanto Putra, Rosdiana (Journal of Technical Education and Training, 2022)
This study aims to analyze the pedagogical competence needs of vocational lecturers. Learning development problems and needs related to the preparation of vocational lecturers can produce skilled vocational lecturers. The research method used is a quantitative method through surveys by distributing questionnaires given to vocational lecturers at Polytechnics in West Java, Indonesia. The findings obtained are the level of understanding of lecturers about students’ background is 76%. 82% of lecturers have compiled a complete Lesson Plan, both for activities in the classroom and outside the classroom. Mastery of the application of learning materials, media, methods, and laboratory equipment for vocational lecturers is very high, above 83%. This is in line with the characteristics of vocational education which must prepare students or graduates to quickly adapt to the workplace environment. However, in the activity of quiz making through online media, it is classified as a moderate at 68%, whereas the online learning and evaluation methods are beneficial since these methods are quite effective. The ability of vocational lecturers in conducting pretests before learning activities has a low score at 76%. This finding indicates that there are many difficulties, one of the factors is not knowing the urgency of the assessment. The pedagogical competence of vocational lecturers has an important role in the success of learning, both in the classroom and during practice. The benefit of this research is that the data obtained can be used as the basis for determining curriculum policies and vocational lecturer training programs to increase human resources following vocational lecturer programs in the industry 4.0 era.